(untitled) (Jurnal Ecosolum, 2023)
The high level of clay and the predominance of 2:1 montmorillonite clay on the soil affect the swelling and shrinking of Vertisols soils, inhibiting plant rooting. This study aims to determine the way of giving and the amount of water in Vertisols soil from Jeneponto Regency, Province of South Sulawesi, Indonesia. This research is an experimental pot in a greenhouse, Faculty of Agriculture, Hasanuddin University, Indonesia. This study used a two-factor block random design method, namely the water provision factor consisting of 2 treatments and the water content factor consisting of 4 treatments with three repeats so that 24 treatment pots were obtained. The water is given through the surface and drops with a water content of 100%, 75%, 50%, and 25% of the field capacity. The results showed that the Vertisols Jeneponto had an available waterwater content of 24.60% (field capacity water content of 40.80% and permanent wilting point of 16.20%) with a clay content of 82%. The water provision method affects the width and depth of the fracture as the vegetative and root growth of maize. The results also showed that continuously applying water in limited quantities (drips method with a water content of 75% of field capacity) directly into the root area of plants can suppress the occurrence of shrinking and increase vegetative and root growth of maize as well as the use of a smaller amount of water compared to the surface method.